Menyusun Materi Presentasi Menggunakan Power Point (PPT) - Harmastuti; Uminingsih (DHARMA BAKTI, 2022)
Kindergarten is an early education for an early age, in delivering learning material a special approach is needed, interesting and easy to understand. GOPTKI is the Association of Indonesian Kindergarten Organizing Organizations which always strives to improve the quality of teacher human resources. One of them is providing training on how to deliver learning materials.On this occasion GOPTKI collaborated with the Department of Computer Systems Engineering and Informatics IST AKPRIND Yogyakarta, to provide training in Microsoft Word, Microsoft Power Point and Internet Browsing. Here the main emphasis is on Microsoft Power Point training and internet access to create presentation materials. Introduce existing facilities and try to insert pictures of animals, parks on, Microsoft Power Point environment and arrange photo albums.The results of the training of teachers are very enthusiastic in trying to use Microsoft Power Point and can use the existing facilities.